Genetic analysis and molecular mapping of resistance to bacterial leaf pustule disease in soybean: Genetic analysis and molecular mapping of resistance to bacterial leaf pustule disease in soybean - S P TOTADE; S K GUPTA; J G MANJAYA (Journal of Oilseeds Research, 2023)
Bacterial leaf pustule (BLP) caused by Xanthomonas axonopodis pv. glycines (Xag) is a serious disease of soybean. A resistant source ‘TS 3’ was identified and the inheritance studies indicated that the duplicate recessive genes govern the resistance. The genetic linkage analysis mapped the resistance locus (rxp-2) on chromosome 2 flanked by the SSR markers Sat_183 and BARCSOYSSR_02_1613 at a distance of 0.9cM and 2.1cM respectively. Similarly, another resistance locus (rxp-6) was mapped between the SSR markers BARCSOYSSR_06_0024 and BARCSOYSSR_06_0013 at a distance of 1.5cM and 2.1cM respectively.